Operationalizing a Data to Care Strategy in Michigan Through Cross-Agency Collaborations. (1st September 2019) - Macomber, Kathryn E.; Viall, Abigail; Ramakrishnan, Vishakha; Wilson, Janae; Brandt, Mary-Grace; Kinsinger, Lindsey; Kreiner, Meta; Curtis, Tom; Copeland, Rachel; Staudacher, Amber; Neff, David
Abstract : Background: For persons with HIV infection (PWH), viral load suppression is essential to maintaining health and reducing the likelihood of HIV transmission. Data to Care (D2C) is an important strategy for improving HIV outcomes but may be resource-intensive to execute. Setting: In 2016, Michigan joined the HIV Health Improvement Affinity Group to strengthen D2C partnerships between its Medicaid and HIV program. Goals included establishing routine data sharing, matching data sources to understand health outcomes, and collaborating to turn data into action. Methods: Michigan established data use agreements to assess gaps in care for PWH enrolled in Medicaid. The HIV Surveillance Program used Link Plus to match surveillance records on PWH to Medicaid's active beneficiary file to identify PWH who were beneficiaries as of December 31, 2015. Results: Matching the 2, 300, 877 Michigan Medicaid beneficiaries with the 15, 845 PWH in HIV surveillance yielded 4822 matched PWH enrolled in Medicaid in 2015. Of Medicaid beneficiaries with HIV, 597 had no evidence of receiving HIV care, representing 20% of all Michigan residents with HIV and not in care in 2015. Conclusion: D2C is an effective strategy for improving HIV care continuum outcomes but can be relatively inefficient if implementation models rely solely on public health infrastructure. Through the HIV Health Improvement Affinity Group, Michigan's Medicaid and HIV programs leveraged their combined data assets to evaluate and improve care quality and outcomes for PWH on Medicaid. Partnerships between Medicaid and public health offer attractive mechanisms for potentially increasing efficiency and effectiveness of D2C investments.